"National Champions" in Global Meat Supply Chains: Implications for Governance and Corporate Power in Food Systems - Katherine Sievert; Philip H. Howard; Alexandre San Martim Portes; Marina Yamaoka (The Journal of Peasant Studies, 2025)
National champion policies in BRICS countries pose challenges for governance in global meat processing markets as they increase concentration, reduce competition and enhance corporate power in food systems. We investigate the degree to which these shifts benefit sponsoring governments and citizens relative to intervention levels. By analysing mergers and acquisitions involving these firms, we unveil coordinated growth strategies benefiting primarily transnational capitalist investors. Our findings underscore the need for heightened scrutiny of national champion mergers and consideration of stronger international antitrust regulation. Understanding the evolving corporate power dynamics in meat supply chains is essential for improved ecological and social outcomes.
Keywords: P1; L66; Q18; G34; 330; capital as power; concentration; corporation; dominant capital; ecology; food; mergers & acquisitions